2020
DOI: 10.1038/s41598-020-67141-z
|View full text |Cite|
|
Sign up to set email alerts
|

Positive-negative tunable liquid crystal lenses based on a microstructured transmission line

Abstract: In this work, a novel technique to create positive-negative tunable liquid crystal lenses is proposed and experimentally demonstrated. This structure is based on two main elements, a transmission line acting as a voltage divider and concentric electrodes that distribute the voltage homogeneously across the active area. This proposal avoids all disadvantages of previous techniques, involving much simpler fabrication process (a single lithographic step) and voltage control (one or two sources). In addition, low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…In previous numerical studies, we have revealed that the maximum relative deviation occurs at the mid-point of the inter-electrode gap. This value increases exponentially as the aspect ratio of the cell thickness over the gap becomes less than unity 40 .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In previous numerical studies, we have revealed that the maximum relative deviation occurs at the mid-point of the inter-electrode gap. This value increases exponentially as the aspect ratio of the cell thickness over the gap becomes less than unity 40 .…”
Section: Introductionmentioning
confidence: 98%
“…Recently, we proposed a solution that overcomes the aforementioned shortcomings by employing a voltage transmission electrode and a set of closely spaced concentric electrodes 40 . The proposed device behaves like a multielectrode modal lens but with simple fabrication process and voltage control, using only one or two low-voltage signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a restriction between tunable range of lens power and aperture size because of the limitation of birefringence of LC materials [6]. To overcome this obstacle, LC lenses based on multiple ring-shaped electrodes [7], Pancharatnam-Berry phase type [8] and Fresnel type [9] are proposed.…”
Section: Introductionmentioning
confidence: 99%
“…It combines all the advantages of previous structures but fabrication and voltage control are much simpler and straightforward. By exploiting this technique, we have recently demonstrated axicon and spherical lenses [52], cylindrical and Powell lenses [53] and mutioptical systems [54].…”
Section: Introductionmentioning
confidence: 99%